Coalition formation in international environmental agreements and the role of institutions - Giulio Ecchia; Marco Mariotti (Fondazione Eni Enrico Mattei (FEEM), 1998)
The aim of this paper is to discuss the role played by international institutions in achieving effective International Environmental Agreements. We emphasise the strategic nature of environmental negotiations and use a game theoretic model of coalitional bargaining to illustrate the main issues. We argue that international institutions can intervene in the framing of the strategic interactions between countries (i.e. setting the rules of the negotiation game) and can influence the actual agreement reached when different outcomes of the negotiation game can be equilibria.
Keywords: Q3; C7; 330; Coalition formation; Environmental agreements; Institutions; Bargaining; Co-operation; Umweltabkommen; Internationale Organisation; Spieltheorie; Koalition; Theorie